To calculate \( 4.8 \times 10^{-3} - 9.4 \times 10^{-6} \), we first need to express both terms with the same exponent of \( 10 \).
Let's rewrite \( 4.8 \times 10^{-3} \) in terms of \( 10^{-6} \):
\[ 4.8 \times 10^{-3} = 4.8 \times 10^{-3} \times \frac{10^{3}}{10^{3}} = 4.8 \times 10^{3} \times 10^{-6} = 4.8 \times 1000 \times 10^{-6} = 4800 \times 10^{-6} \]
Now we can subtract \( 9.4 \times 10^{-6} \) from \( 4800 \times 10^{-6} \):
\[ 4800 \times 10^{-6} - 9.4 \times 10^{-6} = (4800 - 9.4) \times 10^{-6} = 4790.6 \times 10^{-6} \]
Next, we convert \( 4790.6 \times 10^{-6} \) to scientific notation:
\[ 4790.6 = 4.7906 \times 10^{3} \]
Thus,
\[ 4790.6 \times 10^{-6} = 4.7906 \times 10^{3} \times 10^{-6} = 4.7906 \times 10^{-3} \]
Now we round this to 2 decimal places:
\[ 4.7906 \approx 4.79 \]
Finally, the answer in scientific notation rounded to 2 decimal places is:
\[ \boxed{4.79 \times 10^{-3}} \]